La estrategia didáctica “Aprendiendo juntos” y su influencia en los niveles de comprensión lectora de textos narrativos en niños/as del 3er grado de primaria en la I.E José Carlos Mariátegui - Mosquera Díaz, Jhon Willy (2012)
The present investigation answers to the general problem: ¿ What measure the didactic strategy influences " Learning together " in the improvement of the levels of reading comprehension of narrative texts in children and girls of the Third degree of Primary Education, Educational Experimental lnstitution José Carlos Mariátegui, Sector Rupacucha, district of Rioja, 201 O?, Before which we appear the following general hypothesis: lf we experience the didactic Strategy " Learning together " then it will improve the levels of reading comprehension of narrative texts in children and girls of the Third degree of Primary Education, Educational Experimental lnstitution Jose Carlos Mariátegui, Sector Rupacucha, district of Rioja, 201 O, it is developed to choose the teacher's Title of Primary Education in the Faculty of Education and Humanities- Rioja of the National University of St Martín. The methodology is of type technological, follows the experimental method and the pre-experimental design with an alone group with pre and posttries. The withdrawal of information did to itself by means of a questionnaire that it contains ítems of the variable of study, applied to a sample of children and girls of the mentioned degree, being this one not probabilística, the above mentioned representation it is given on the basis of an opinion or particular intention of the author of the investigation. The most important conclusions we can indicate that in the test of principal hypothesis, on the influence of the didactic strategy in the reading comprehension, it shows the obtained results product of the utilization of the statistical formulas (comparison pareada) for the check of the hypothesis, a value being obtained calculated of te = -9,37 and a value to tabulate of t1 = 1,796 ( obtained of the table of probability of the distribution t of Student, with a level of significancia of 5 % and 11 degrees of freedom), checking that the calculated val u e is minor that the value tabulates left-handed, who allows that the void hypothesis should be located inside the region of rejection. Consequently it is decided to accept the hypothesis of investigation with a confidence level of 95 %. Meaning that, the didactic strategy "Learning Together ", Jose Carlos Mariátegui has influenced significantly in the levels of reading comprehension of narrativa texts in children and girls of the third degree of the level of Primary Education in the Educational Experimental lnstitution, Sector Rupacucha, district of Rioja, for what we think that we have reached the general objective.